Les temps de la catastrophe - Jérémy Desarthe (EchoGéo)
The hurricane of September 1928 which struck the Antilles and especially the Guadeloupe constitutes one of the most important natural disasters that experienced this territory during the XXth century. From the use of the available archives, it is possible to analyze the consequences of the event through the damage inventoried and the assistance implemented. So, it is possible to apprehend the different temporality of the disaster until 1934.